MRI-based assessment and characterization of epicardial and paracardial fat depots in the context of impaired glucose metabolism and subclinical left-ventricular alterations - Rado, Sophia D; Lorbeer, Roberto; Gatidis, Sergios; Machann, Jürgen; Storz, Corinna; Nikolaou, Konstantin; Rathmann, Wolfgang; Hoffmann, Udo; Peters, Annette; Bamberg, Fabian; Schlett, Christopher L. (British journal of radiology, 2019)
Objective: To analyze the associations between epicardial and paracardial fat and impaired glucose tolerance as well as left ventricular (LV) alterations. Methods: 400 subjects underwent 3 T MRI and fat depots were delineated in the four chamber-view of the steady-state free precession cine sequence (repetition time: 29.97 ms; echo time 1.46 ms). LV parameters were also derived from MRI. Oral glucose tolerance tests were performed. Results: Epi- and paracardial fat was derived in 372 (93%) subjects (220 healthy controls, 100 persons with prediabetes, 52 with diabetes). Epi- and paracardial fat increased from normal glucose tolerance (NGT) to prediabetes and diabetes (7.7 vs 9.2 vs 10.3 cm2 and 14.3 vs 20.3 vs 27.4 cm2, respectively; all p < 0.001). However, the association between impaired glucose metabolism and cardiac fat attenuated after adjustment, mainly confounded by visceral adipose tissue (VAT). 93 subjects (27%) had LV impairment, defined as late gadolinium enhancement, ejection fraction < 55% or LV concentricity index > 1.3 g ml−1 . Mean epicardial fat was higher in subjects with LV impairment (11.0 vs 8.1 cm2, p < 0.001). This association remained independent after adjustment for traditional risk factors and VAT [β: 1.13 (0.22; 2.03), p = 0.02]. Conclusion: Although epicardial and paracardial fat are increased in prediabetes and diabetes, the association is mostly confounded by VAT. Epicardial fat is independently associated with subclinical LV impairment in subjects without known cardiovascular disease. Advances in knowledge: This study contributes to the picture of epicardial fat as a pathogenic local fat depot that is independently associated with MR-derived markers of left ventricular alterations.